Change in diagnosis and treatment following specialty voice evaluation: A national database analysis. (13th February 2015) - Cohen, Seth M.; Kim, Jaewhan; Roy, Nelson; Wilk, Amber; Thomas, Steven; Courey, Mark
<x xml:space="preserve">Abstract</x> Objective We evaluated the association between specialty voice evaluation and changes in laryngeal diagnosis and treatment in patients with laryngeal/voice disorders. Study Design Retrospective analysis of a large, national administrative U.S. claims database. Methods Patients included were identified with a laryngeal disorder based on International Classification of Diseases, Ninth Revision, Clinical Modification codes, from January 1, 2004, to December 31, 2008, and had been seen by an otolaryngologist as an outpatient and had a specialty voice evaluation designated by videolaryngostroboscopy (VLS) within 90 days of the last laryngoscopy. Patient diagnosis at the last laryngoscopy visit and the subsequent initial VLS visit were collected. Specific treatment modalities were tabulated for the 30‐day period after the last laryngoscopy and for 30 days after the VLS. Results A total of 168, 444 unique patients saw an otolaryngologist for 273, 616 outpatient visits. Of those, 6.1% had a VLS performed, of which 4, 000 (23.8%) occurred within 90 days of the last laryngoscopy, with a median interval of 30 days (interquartile range 15–50 days). Half of the patient visits had a change in laryngeal diagnosis. Changes in use of antibiotics, proton pump inhibitors, voice therapy, and surgical intervention were seen after specialty voice evaluation. Conclusions Specialty voice evaluation was associated with changes in laryngeal diagnosis and treatment. Further study is needed to assess the impact on health care costs and patient outcomes. Level of Evidence 2b. Laryngoscope, 125:1660–1666, 2015